SHORTAGEFLATION 3.0: WAR ECONOMY, STATE SOCIALISM, AND PANDEMIC CRISIS - Grzegorz W. Kolodko (Revista Tempo do Mundo, 2021)
The crisis caused by the coronavirus pandemic has prompted governments and central banks to take unorthodox measures aimed at protecting the standard of living of people and sustaining the production and service activities of companies. The policy of aggressively raising the supply of money has entailed a significant increase in the budget deficit and public debt. It is important to consider the extent of its impact on the escalation of inflation processes and to formulate suggestions regarding economic policy. Inflation is already higher than the official indicators show because it is partly suppressed. The increase in the general price level does not fully reflect the actual inflation rate. We are dealing with shortageflation – the simultaneous occurrence of price inflation and repressed inflation accompanied by shortages. It is methodologically interesting to compare this current phenomenon, 3.0, with the suppression of inflation in the war economy, 1.0, and in the economies of state socialism, 2.0. Such comparisons highlight not only the similarities of these processes but also differences resulting from the specificity of responses of households and businesses. This article discusses five channels of unloading excessive savings, indicating the most beneficial ones from the point of view of sustainable economic development in the post-pandemic future. It is particularly important to prompt the conversion of compulsory savings into voluntary savings and at the same time to stimulate the transformation of the inflationary monetary reserves into effective demand expanding the use of existing production capacities and investments creating new capacities.